Genome-wide analysis of tandem duplicated genes and their expression under salt stress in seashore paspalum - Hu, Xu; Hao, Jiangshan; Pan, Ling; Xu, Tao; Ren, Longzhou; Chen, Yu; Tang, Minqiang; Liao, Li; Wang, Zhiyong (Frontiers in Plant Science, 2022)
Seashore paspalum (Paspalum vaginatum) is a halophytic, warm-season grass which is closely related to various grain crops. Gene duplication plays an important role in plant evolution, conferring significant plant adaptation at the genomic level. Here, we identified 2,542 tandem duplicated genes (TDGs) in the P. vaginatum genome and estimated the divergence time of pairs of TDGs based on synonymous substitution rates (Ks). Expression of P. vaginatum TDGs resulted in enrichment in many GO terms and KEGG pathways when compared to four other closely-related species. The GO terms included: “ion transmembrane transporter activity,” “anion transmembrane transporter activity” and “cation transmembrane transport,” and KEGG pathways included “ABC transport.” RNA-seq analysis of TDGs showed tissue-specific expression under salt stress, and we speculated that P. vaginatum leaves became adapted to salt stress in the earlier whole-genome duplication (WGD; ~83.3 million years ago; Ma), whereas the entire P. vaginatum plant acquired a large number of TDGs related to salt stress in the second WGD (~23.3 Ma). These results can be used as a reference resource to accelerate salt-resistance research in other grasses and crops.